Primary Fallopian Tube Carcinosarcoma: A Rare Case Report - Shresha, Eliza; Bista, Kumar Bahadur; Kunwar, Radhika; Mally, Jasma; Basi, Trishala; Bhat, Hari Rana (Nepalese Journal of Cancer, 2025)
The carcinomasarcoma of Fallopian tube is a rare gynecologic tumor. Fewer than 100 cases are reported in the literature. We present the case of a 51-years-old with irregular per vaginal bleeding since 4 months. Magnetic resonance imaging (MRI) revealed a solid, lobulated left ovarian mass measuring 6.9 × 4.9 × 4.4 cm, with a dilated and tortuous fallopian tube measuring 1.6 cm in diameter. Her CA-125 level was 217 U/mL. Surgical staging included total abdominal hysterectomy, bilateral salpingo-oophorectomy, bilateral pelvic lymph node dissection, and infracolic omentectomy. Histopathology confirmed carcinosarcoma of the left fallopian tube with ovarian surface involvement. She subsequently received three cycles of carboplatin (500 mg) and paclitaxel (285 mg). At 6 months’ follow-up, tumor markers and imaging remained normal with no evidence of recurrence. Given the rarity of this condition, case reporting with follow-up details adds valuable insight into diagnostic and treatment efficacy.